Desain Intensitas Penerangan dengan Tipe Jenis Lampu untuk Kegitan Praktikum di Laboratorium Mesin Listrik dan Pengukuran - Dwi Setyawan; Massus Subekti (Jurnal Pengelolaan Laboratorium Pendidikan, 2021)
Lighting planning in a laboratory room is one of the factors in designing to produce good and energy efficient lighting. To carry out all activities in the room of a laboratory, sufficient lighting intensity is needed, so that it can be carried out optimally, especially with regard to practicum work carried out in the laboratory for the benefit of the learning process. In terms of quality, lighting in a room is in the form of strong lighting or illumination level. The purpose of this research is to design, identify and evaluate the recommended lighting intensity / quality with the lighting standards from the existing lamp data installed in the electrical and measurement laboratory. The results of the measurement research for the Electrical Machinery and Measurement Laboratory obtained that the average light intensity for the work point of the practicum table is 127 lux, so that the light intensity is still low according to the SNI 16 - 7062 - 2004 standard with a measuring point of even lighting distribution obtained by 137 lux. If the light intensity of a laboratory is not fulfilled, it will result in inconvenience for students in carrying out the measurement practice, especially for practicum electrical circuits by calculating the value of the ring resistor. For this reason, the intensity of lighting in the laboratory room must be designed to meet the recommended lighting standards for a laboratory, namely 300 lux, namely by adding the number of 8 points of TL Philips Lifemark 36W / 54-765 lamps,or 8 points of 25 W / 2600 lumens LED lamps, or 6 Philips CLF 55 W / 3465 lumen type light point.